Experimental investigation on fracture resistance behavior of additivemanufacturedmultimaterial structure with corrugated interface - Arumaikkannu, G. (2016)
It has been a curiosity and the need which has prompted many researchers to work in the area of design and manufacturing for the possibility of building polymer parts with complex shape using additive manufacturing [AM]. As interactions at interfaces have long been of interest in the area of composite materials and adhesive bonding, similar issues need to be addressed for additive manufactured multi material structures. In this study, a PolyJet system is used to fabricate multi material structure which consists of matrix layers (Tango black plus) sandwiched by two reinforcement layers (Vero white).In this work, interface between reinforcement and matrix layer in flat and corrugated shape (sine-wave ridged pattern) is employed. Corrugated shape is commonly found in nature and engineering structure in order to produce a compliant bending was employed in AM multi material structure to enhance its flexural properties. A common experimental approach to characterize shear performance, were evaluated to characterize the fracture resistance of the interface layers with flat and corrugated structures. Experimental results show that corrugated shape interface has the ability to induce passive shear behavior on AM multi material structures than flat shape interface. From this investigation it can be concluded that interface layer with mechanical linkage such as corrugated shape interfaces shows promising results on performance and durability of AM multi material structure.